Global and regional consequences of the Chinese Belt and Road Initiative - Choroś-Mrozowska, Dominika (Globalna i regionalne konsekwencje inicjatywy pasa i szlaku, 2019)
In the face of challenges that the world will be facing in the near future, numerous ideas have arisen seeking to address the problems of the modern world economy. Of necessity are improvements in the international trading and investment system, as well as the creation of a global value chain (GVC) – beneficial to all participants. One of the more significant initiatives which can contribute to tackling the challenges facing the contemporary global economy is the Chinese Belt and Road Initiative (BRI), colloquially known as the New Silk Road. As part of the BRI, China aims to not only accrue economic benefits for itself, but also to become a regional and possibly global leader, which can introduce modernity into regions that the world has “forgotten”. Given the above, the aim of this work is to discuss the BRI initiative and to identify the consequences of its implementation, both regionally and across the entire global economy. This is particularly important in light of growing international opinion that we are in fact witnessing a new form of globalization – referred to by some, as Chi-globalization. The question is, can China really drive this new world order?
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 6, s. 9-21
Keywords: Belt and Road Initiative; global economy; globalization; trade; inicjatywa Pasa i Szlaku; globalna gospodarka; handel; globalizacja